Sotorasib resistance triggers epithelial-mesenchymal transition and activates AKT and P38-mediated signaling - Megid, Raquel Arantes; Ribeiro, Guilherme Gomes; Gomes, Izabela Natalia Faria; Laus, Ana Carolina; Ferro Leal, Letícia; Sussuchi da Silva, Luciane; Ariwoola, Abu-Bakr Adetayo; Dias, Josiane Mourão; Reis, Rui Manuel; Jose da Silva-Oliveira, Renato (Frontiers in Molecular Biosciences, 2025)
BackgroundThe molecular non-genetic changes of resistance to sotorasib are currently uncertain. The aim of this study was to generate a sotorasib-resistant cell line via selective pressure and systematically examine the molecular and phenotypic alterations caused by resistance.MethodsMutant NCI-H358 (KRASG12C) were exposed to incremental doses (2–512 nM) of sotorasib. Then, resistant clones were separated by single-cell sorting. Proliferation was analyzed in real-time by xCELLigence; protein profiles were quantified by protein arrays; and mRNA expression profile was measured using the PanCancer Pathways panel by NanoString. In silico analyses were conducted from a database comprising patient-derived xenograft (PDX) models and cell lines resistant to sotorasib. AKT and p38. The synergistic effect of combining AKT, p38, and EGFR inhibitors was assessed using the SynergyFinder platform. Additionally, AKT and p38 genes were silenced using esiRNA.ResultsSotorasib-resistant H358-R cell line displayed markers of the mesenchymal-epithelial transition and loss of cell adhesion. Were identified 30 overexpressed genes in the resistance model, implicating in signaling pathways that leads to AKT activation and heightened protein expression levels of phosphorylated AKT and p38. To identify potential therapeutic strategies for overcoming sotorasib resistance, we investigated the combination of AKT and p38 inhibitors. Notably, combined inhibition of AKT (MK2206) and p38 (adezmapimod) restored sensitivity to sotorasib in resistant cell lines, as did silencing AKT expression.ConclusionThese findings underscore the importance of adaptive mechanisms in sotorasib resistance in NSCLC cells contributing by EMT activation and demonstrates synergic combination with AKT and p38 inhibitors to restore sotorasib sensitivity in KRASG12C cells.